2004
DOI: 10.3998/ark.5550190.0005.414
|View full text |Cite
|
Sign up to set email alerts
|

15-Membered triolefinic macrocycles, their coordination chemistry with transition metals, and the catalytic properties of their palladium metal complexes. A review.

Abstract: (E,E,E)-1,6,11-Tris(arenesulfonyl)-1,6,11-triazacyclopentadeca-3,8,11-trienes, 1, are prepared from arenesulfonamides and trans-1,4-dibromo-2-butene. Macrocycles 1 coordinate palladium(0), platinum(0), and silver(I), and the palladium complexes are useful and reutilizable catalysts or precatalysts in Suzuki cross-couplings, butadiene telomerizations, hydroarylation of alkynes, and in the Heck reaction. Structurally related macrocycles are also available by similar synthetic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Olefin-stabilized palladium complexes, which are well described by the Dewar−Chatt−Duncanson model, generally suffer from low stability due to the ease with which olefins are displaced or dissociated from the metal, and this may explain their underexploitation as spectator ligands (ligands coordinated to the metal during catalysis possibly influencing its catalytic properties) in palladium-catalyzed reactions. Exceptions to this are the well-known Pd 2 (dba) 3 (dba) (dba = dibenzylideneacetone), which has been widely used as a catalyst and precatalyst in many palladium-catalyzed transformations, and a novel type of Pd 0 complexes with 15-membered triolefinic aza-macrocyclic ligands described by ourselves (Figure ), which have shown unusual stability for Pd−alkene complexes and demonstrated their potential catalytic activity in Suzuki−Miyaura and Mizoroki−Heck reactions. 2h,i A further more recent exception is the description of a chiral Pd 0 tetraolefin complex by Trauner et al, which shows catalytic activity in enyne cyclization processes 2j 1 Structure of 15-membered triolefinic macrocyclic Pd 0 complexes. …”
Section: Introductionmentioning
confidence: 99%
“…Olefin-stabilized palladium complexes, which are well described by the Dewar−Chatt−Duncanson model, generally suffer from low stability due to the ease with which olefins are displaced or dissociated from the metal, and this may explain their underexploitation as spectator ligands (ligands coordinated to the metal during catalysis possibly influencing its catalytic properties) in palladium-catalyzed reactions. Exceptions to this are the well-known Pd 2 (dba) 3 (dba) (dba = dibenzylideneacetone), which has been widely used as a catalyst and precatalyst in many palladium-catalyzed transformations, and a novel type of Pd 0 complexes with 15-membered triolefinic aza-macrocyclic ligands described by ourselves (Figure ), which have shown unusual stability for Pd−alkene complexes and demonstrated their potential catalytic activity in Suzuki−Miyaura and Mizoroki−Heck reactions. 2h,i A further more recent exception is the description of a chiral Pd 0 tetraolefin complex by Trauner et al, which shows catalytic activity in enyne cyclization processes 2j 1 Structure of 15-membered triolefinic macrocyclic Pd 0 complexes. …”
Section: Introductionmentioning
confidence: 99%
“…13 The type of terminal group can be tuned at will, but we decided to choose 15-membered triolefinic triazamacrocycles. 14 Indeed, these types of macrocycle were previously demonstrated by some of us to be able to afford nanoparticles in mild conditions, starting from organometallic precursors. 15 Palladium nanoparticles were obtained from these types of macrocycle containing several long perfluorinated and long polyoxyethylene chains.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, (the late) Moreno-Mañas, Roglans, and co-workers have shown that N -SO 2 Ar-substituted 1,6,11-triazacyclopentadeca-all- trans -3,8,13-trienes, comprising a 3-fold 1,6-diene sequence in the cycle, form extraordinarily stable Pd(0) complexes A , which decompose only above 250 °C . This result, which is in sharp contrast to the so far inaccessible (t,t,t/c,c,c-cdt)Pd with a 1,5-diene sequence, can be rationalized in terms of the macrocyclic effect .…”
Section: Introductionmentioning
confidence: 98%